Desenvolvimento de produto conceitual: órtese de membro inferior para crianças com Zika congênita - Regis, Thamyris de Sales (2021)
Due to the severe neurological damage presented by children with Congenital Zika (CZ), studies show motor patterns that characterize an unusual type of Cerebral Palsy (CP). Indication of orthotics in treatments of individuals with neurological dysfunctions has been used as a way to assist in the indicated treatment due to its numerous benefits. Thus, the present study aims to develop a conceptual model of lower limb orthotics for children with CZ. A prospective and bibliographic cohort study Was conducted The study was conducted at the Professor Joaquim Amorim Neto Research Institute (IPESQ) in partnership with the Center for Strategic Health Technologies (NUTES) of the State University of Paraíba, both located in the city of Campina Grande, Paraíba, Brazil. Forty-eight children were evaluated, in their physical aspects such as tone and range of motion of the ankle and foot. Statistical analysis was performed using epi info and Medcalc software. In the evaluation of children with CM, when comparing the pattern of ankle deformities among children with CZ and that described in the literature as predominant in CP, it was observed that they present different patterns, reinforcing the need for studies that deepen the monitoring of the development of children with CM throughout life. After gathering this information, a conceptual model of lower limbs orthosis was developed that may provide greater efficacy to the studied public.